4 - La sécurité foncière sur les périmètres irrigués du Burkina Faso: le cas de la vallée du Sourou: 10.4314/ad.v27i1.22156 - Dialla, Basga Emile (Africa Development, 2002)
Land irrigation policy in Burkina Faso is a complementary strateg}7 to agricultura development efforts that are often hampered by rain uncertainty. However, land tenure law does not yield ownership to farmers settled in these irrigated areas. Such a situatio significantly affects their productivity. This article explores the subject through a critic analysis of the law regulating land ownership in Burkina Faso, and from data collected down the Sourou valley. Beyond the issue of land tenure security, is the issue whether or not new operators should be allowed to take over and run efficiently these irrigated area implemented at high cost.